2022
DOI: 10.3390/diagnostics12061463
|View full text |Cite
|
Sign up to set email alerts
|

Practical Approach to Histological Diagnosis of Peripheral Nerve Sheath Tumors: An Update

Abstract: Peripheral nerve sheath tumors encompass a wide spectrum of lesions with different biological behavior, including both benign and malignant neoplasms as well as the recent diagnostic category, i.e., “atypical neurofibromatous neoplasm with uncertain biologic potential” to be used only for NF1 patients. Neurofibromas and schwannomas are benign Schwann-cell-derived peripheral nerve sheath tumors arising as isolated lesions or within the context of classical neurofibromatosis or schwannomatoses. Multiple tumors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 88 publications
(135 reference statements)
1
21
0
2
Order By: Relevance
“…Histologically, diffuse neurofibromas are described to be unencapsulated spindle cell tumors with bland cytologic appearance, serpiginous nucleo-cytoplasmic contours, and poorly delimited boundaries with the surrounding dermis [ 10 ]. This was the histopathological picture seen in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, diffuse neurofibromas are described to be unencapsulated spindle cell tumors with bland cytologic appearance, serpiginous nucleo-cytoplasmic contours, and poorly delimited boundaries with the surrounding dermis [ 10 ]. This was the histopathological picture seen in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical schwannomas require a combination of immunohistochemical findings to differentiate them from tumors such as neurofibromas and solitary circumscribed neuroma ( 23 ). S-100 and SOX10 are recognized positive markers, but the ancillary role of other markers, such as EMA, INI-1, and TTF-1, in the diagnosis is rarely discussed and demonstrated ( 24 ). In this study, we verified the high positive rate of S-100 and SOX in schwannomas and identified several immunohistochemical markers that could be used as potential adjunctive diagnostic markers, such as Ki-67 and β-Catenin, which had high positive rates, and SDH8, Vimentin, H3K27Me3, and Fli-1, which stained a small number of cases but achieved 100% positive rate, and perhaps they can be tested more in future immunohistochemistry to obtain more data.…”
Section: Discussionmentioning
confidence: 99%
“…For example, sarcomatous transformation may occur in benign nerve sheath tumors and rarely in (noncentral) atypical lipomatous tumors, or carcinoma may evolve from pleomorphic adenoma, but the non-cancer label must remain for their pure nontransformed form. [76][77][78] A similar argument also applies to the reasoning that molecular alterations in higher GGs are seen in GG 1 as it is known that borderline tumor, tumor of LMP, and dysplasia also overlaps genomically with invasive carcinoma. 75,[79][80][81] As mentioned, most of the arguments for keeping the cancer label in GG 1 are scenarios related to current uncertainties inherent in the biopsy process.…”
Section: Main Arguments and Counterarguments Against Renaming Grade G...mentioning
confidence: 90%
“…A pathologic diagnosis should be the reflection of its current state and form and not its future transformation, like a snapshot along its disease course. For example, sarcomatous transformation may occur in benign nerve sheath tumors and rarely in (noncentral) atypical lipomatous tumors, or carcinoma may evolve from pleomorphic adenoma, but the non-cancer label must remain for their pure nontransformed form 76–78 . A similar argument also applies to the reasoning that molecular alterations in higher GGs are seen in GG 1 as it is known that borderline tumor, tumor of LMP, and dysplasia also overlaps genomically with invasive carcinoma 75,79–81 …”
Section: Main Arguments and Counterarguments Against Renaming Grade G...mentioning
confidence: 98%